2020
DOI: 10.1101/2020.04.17.046201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissociable electrophysiological measures of natural language processing reveal differences in speech comprehension strategy in healthy ageing

Abstract: Healthy ageing leads to changes in the brain that impact upon sensory and cognitive processing. It is not fully clear how these changes affect the processing of everyday spoken language. Prediction is thought to play an important role in language comprehension, where information about upcoming words is pre-activated across multiple representational levels.However, evidence from electrophysiology suggests differences in how older and younger adults use context-based predictions, particularly at the level of sem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 42 publications
5
29
4
Order By: Relevance
“…In Broderick et al (2020), the greatest age-related differences were shown for semantic dissimilarity, whereas our goodness-of-fit results showed relatively weak contributions from this feature (compared to surprisal and word audibility) that did not differ significantly between the younger and older age groups. However, we did observe greater frontal TRF deflections in the older group for dissimilarity, with significant group differences around 250 and 600 ms, suggesting an increased gain for this feature in the older population.…”
Section: Relationship To Existing Work On Age-effects On Electrophysicontrasting
confidence: 64%
See 4 more Smart Citations
“…In Broderick et al (2020), the greatest age-related differences were shown for semantic dissimilarity, whereas our goodness-of-fit results showed relatively weak contributions from this feature (compared to surprisal and word audibility) that did not differ significantly between the younger and older age groups. However, we did observe greater frontal TRF deflections in the older group for dissimilarity, with significant group differences around 250 and 600 ms, suggesting an increased gain for this feature in the older population.…”
Section: Relationship To Existing Work On Age-effects On Electrophysicontrasting
confidence: 64%
“…Studies comparing envelope-related cortical responses have revealed a pattern of amplified envelope representations in older populations (Presacco et al, 2016;Decruy et al, 2019;Zan et al, 2020), potentially reflecting changes in the utilization of cognitive resources during speech comprehension. More recently, Broderick et al (2020) compared higher-level representations of speech in younger and older populations. They estimated EEG responses to 5-gram surprisal, reflecting the predictability of words given the preceding sequence of four words, as well as semantic dissimilarity, reflecting the contribution of each word to the semantic content of a sentence.…”
Section: While Development Of Behavioral Paradigms Focusing On Characmentioning
confidence: 99%
See 3 more Smart Citations